The Influence of Product Quality, Service Quality, and Security on Generation Z Customer Loyalty After the Migration of BSI Mobile to Byond by BSI in Jabodetabek - Hilmi Nisa; Endah Setyowati (Falahiya Journal of Islamic Banking and Finance, 2025)
Introduction: Digital transformation is a key strategy to increase customer loyalty. BSI migrated from BSI Mobile to Byond by BSI to improve services, but this change raises new challenges related to the perception and loyalty of Generation Z customers. Therefore, it is necessary to examine the response of Generation Z to the service migration. Research Methods: This type of research is quantitative with a comparative and associative approach. Data were obtained by distributing questionnaires to 97 respondents, namely Generation Z in Jabodetabek who use BSI Mobile and Byond by BSI. Results: The results of the study showed significant differences in product quality, service, security, and loyalty before and after migration to Byond by BSI, with a significance value of 0.000 <0.05. Partially, the three variables have a significant effect on customer loyalty, as well as simultaneously. The R² value of 0.534 indicates that 53.4% of the variation in customer loyalty is explained by the three variables. Conclusion: Improving digital quality through Byond by BSI has proven to have an impact on increasing the loyalty of Generation Z customers in the Jabodetabek area.